The villainess's guide to (not) falling in love. 4 - Touya; Yoimachi (Light novel illustrator) (Square Enix Manga & Books, 2025)
"Can one would-be villainess fend off multiple handsome suitors' advances to simply live a peaceful life? Or will the game force a happy ending no matter what? Light conversation at the Wisterias' gorgeous banquet takes a turn when Saphir tells the tale of a certain fateful deal, exposing a connection Luciana never knew existed. Her role in the story may be way more than she ever bargained for! Then the link between third-born Louis and the mysterious fate of the fourth Wisteria brother comes to light... To protect the people she cares about, Luciana's only choice is to confront the Evil Star of the East!"--